TINGKAT KEBUGARAN JASMANI MAHASISWA PENDIDIKAN OLAHRAGA UNIVERSITAS QUALITY BERASTAGI MASA ERA NEW NORMAL TAHUN AKADEMIK 2021/2022 - Janwar Frihasan Sinuraya; Julius Boy Nesra Bagismata Barus (Universitas Quality, 2022)
Sports activities can be associated with health and goal achievement, which includes various aspects, one of which is physical fitness. The Covid-19 outbreak has not been identified in terms of the physical fitness of students majoring in sports, especially during the new normal period. The purpose of this study was to measure the level of physical fitness of sports students. This research is a descriptive research with a survey approach. The demographics and sample of this research are sports students, with a total of 15 students whose data collection was carried out before and after the new normal period of Covid-19. The data collection technique in this study used a physical fitness test instrument consisting of test items, namely a 60-meter run test, a 60-second hanging test, a sit-up test for 60 seconds, an upright jump test, and a 1200-meter run test. The data analysis approach used in this research is descriptive statistical analysis with percentage presentation. Based on the results of the study, the physical fitness of the students of the Sports Education Study Program, Quality Berastagi University very good 1 person (6.67%), good 3 people (20%), moderate 5 people (40%), less than 3 people (20%0 and less than 2 people (13.33%). So it can be concluded that in the new era Normal level of physical fitness is categorized as moderate.